1994
DOI: 10.1111/j.1442-200x.1994.tb03217.x
|View full text |Cite
|
Sign up to set email alerts
|

An early‐onset case of multiple sclerosis with thalamic lesions on MRI

Abstract: We present here an early-onset case of multiple sclerosis (MS) with thalamic lesions. The patient first experienced an episode of ataxic gait at 2 years 3 months of age, with spontaneous remission within 1 month. At 5 years 4 months, she was admitted because of cerebellar ataxia, oculomotor restriction and feeding difficulty. Magnetic resonance imaging (MRI) showed multiple well-defined lesions in the white matter of the cerebellum, mid-brain, periventricle and right frontal lobe. Cerebrospinal fluid (CSF) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Using the conventional, T2-weighted, spin-echo sequence, the presence of demyelinating plaques was demonstrated in the gray matter of some MS patients [48]. The localization of the demyelinating process of MS in the deep gray matter, in particular the thalamus, also emerged in an early-onset case of multiple sclerosis [4]. Furthermore, there is a case report of an R-R MS patient with an initial presentation of myelopathy who had demyelinating lesions located in spinal cord gray matter [54].…”
Section: Discussionmentioning
confidence: 96%
“…Using the conventional, T2-weighted, spin-echo sequence, the presence of demyelinating plaques was demonstrated in the gray matter of some MS patients [48]. The localization of the demyelinating process of MS in the deep gray matter, in particular the thalamus, also emerged in an early-onset case of multiple sclerosis [4]. Furthermore, there is a case report of an R-R MS patient with an initial presentation of myelopathy who had demyelinating lesions located in spinal cord gray matter [54].…”
Section: Discussionmentioning
confidence: 96%
“…, 1994; Tenembaum et al. , 2002), whereas in multiple sclerosis it is rare (Asai et al. , 1994; Masson and Colombani, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As grey matter also contains myeline and oligodendrocytes, the same perivenous inflammatory process and MRI signal abnormalities can occur as in white matter. In cases of ADEM, involvement of deep grey matter nuclei revealed by MRI interestingly seems to be common (Baum et al, 1994;Tenembaum et al, 2002), whereas in multiple sclerosis it is rare (Asai et al, 1994;Masson and Colombani, 2002). Recent studies using diffusiontensor imaging in patients with ADEM have demonstrated the presence of microscopic tissue damage in the basal ganglia of patients with ADEM but not in MS patients with a similar burden of MRI visible brain lesions (Holtmannspotter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating the patterns in the LFB stained brain sections (Figure ), CD3 markers saw the greatest reduction in the cerebellum (Figure A–C) and internal capsule (Figure D–F) regions of the brains of the mice treated with 23 . Although this is an animal model of MS and primarily considered as an inflammation-driven MS model, it is well-characterized that disease pathology such as lesions appearance is localized to cerebellum and internal capsule areas of the brain. …”
Section: Resultsmentioning
confidence: 99%